2021
DOI: 10.1590/1679-78256714
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of high-strength concrete columns interconnected by normal-strength concrete floor

Abstract: The construction methods currently adopted for multi-story concrete buildings resorts the strategy to cast columns and slabs with high and normal compressive concrete strength, respectively. The intersection region affects the load transfer performance of the columns, causing expressive confinement stress in interior columns. However, when the confinement is only provided by two sides, as corner columns, it is not enough to increase the lateral stress. The structural behavior of corner columns, represented by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The influence of concrete strength column‐slab ratio, the steel reinforcement ratio of the column and the beam, beam height and the column width ratio and the largest dimension of the column cross section have been analyzed and the following conclusions can be drawn from the results. The numerical results showed that the parameters with the greatest influence on the stress distribution are the h/c and concrete strengths ratio (fitaliccc/fitaliccs). The interior columns confinement results showed a better performance when compared to the sandwich columns, even though the lateral stress was not integral on all four sides. The concrete strength average increase was 13.7% compared to the sandwich columns 22 The effective compressive strength found in columns with a h/c ratio of 5 was equal to fitaliccs, with the exception of the HSC and NSC ratios (fitaliccc/fitaliccs) of 2.33, 2.67 and 3, which presented increase of approximately 10%. The numerical results for models with a h/c>3.57 ratio had modest strength gains.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The influence of concrete strength column‐slab ratio, the steel reinforcement ratio of the column and the beam, beam height and the column width ratio and the largest dimension of the column cross section have been analyzed and the following conclusions can be drawn from the results. The numerical results showed that the parameters with the greatest influence on the stress distribution are the h/c and concrete strengths ratio (fitaliccc/fitaliccs). The interior columns confinement results showed a better performance when compared to the sandwich columns, even though the lateral stress was not integral on all four sides. The concrete strength average increase was 13.7% compared to the sandwich columns 22 The effective compressive strength found in columns with a h/c ratio of 5 was equal to fitaliccs, with the exception of the HSC and NSC ratios (fitaliccc/fitaliccs) of 2.33, 2.67 and 3, which presented increase of approximately 10%. The numerical results for models with a h/c>3.57 ratio had modest strength gains.…”
Section: Discussionmentioning
confidence: 82%
“…At point C, confining stresses are expected in direction 1. Still, in direction 3, the confinement will be given in general by the same criterion as that of the sandwich column, 22 even though the beam in direction 3 can have a small influence on this confinement.…”
Section: Confinement Of the Interior Columnmentioning
confidence: 99%
See 3 more Smart Citations